(untitled) (Applied Biological Research, 2017)
The study was aimed to evaluate the effect of various categories of feed additives on rumen fermentation. Fermentation kinetics and substrate utilization by rumen microbes was studied by fortifying the substrate having roughage to concentrate of 60:40 with glucogenic viz., glycerol and propylene glycol (PG), rumen fermentation modifiers viz., para aminobenzoic acid (PABA), exogenous fibrolytic enzymes (EFE) and probiotic feed additives by applying first order kinetics model to in vitro gas production (IVGP) technique. Glycerol was more effective than PG for substrate fermentation kinetics and its utilization, particularly IVTVFA production. Buffer addition was more effective with PG but not with glycerol. PABA had non-significant impact on either substrate fermentation kinetics or utilization. EFE fortification significantly improved the extent of fermentation, IVNDFD and IVTVFA; however, probiotics showed only significant increase in IVDMD (P<0.01) and IVTVFA (P<0.05) by 11%. Study concluded that PG and glycerol being glucogenic compounds improved the extent of fermentation and TVFA production but glycerol was more effective than PG. Probiotics supplementation also had positive effect on IVTVFA production. EFE fortification improved fibre digestion. Buffer addition along with feed additives may enhance substrate kinetic efficiency of fermentation but it was selective.